Profil Berpikir Siswa SMP dalam Menyelesaikan Masalah Matematika Ditinjau dari Kemampuan Matematika - Ahmad Isroil; I Ketut Budayasa; Masriyah Masriyah (Department of Mathematics Education, Faculty of Tarbiyah and Teacher Training, UIN Sunan Ampel Surabaya, 2017)
This study has aims to describe the profile of junior high school students’ Thinking in Solving math problems. The subjects of this research are three students of high, medium and low in mathematical ability. Thinking profile of students described as follows: Understanding the problem, students received information by reading problems, then they recalled, processed, and stored information. Devising a plan, students processed, stored, and recalled information. Carrying out the plan, students recalled, processed, and stored information. Looking back, students stored information by performing a repletion of steps looking back.